Model Konseptual E-Da'wah Muhammadiyah Berbasis Web - Nugroho Agung Prabowo; R Arri Widyanto; Bambang Pujiarto; Mukhtar Hanafi; Andi Widiyanto; Meidar Hadi Avizenna (Universitas Muhammadiyah Magelang, 2022)
The development of information and communication technology has been proactively addressed by Muhammadiyah. Muhammadiyah has modernized da'wah methods by utilizing ICT technology in every activity, but it is still limited to media commonly used by the public such as social media, the web on the Internet, and so on, so that it is still limited, partial, and has not been systematic and structured ally serves its people and is constrained in monitoring and evaluation. The use of web based systems can be a solution to develop locations or e-da'wah based on geography while answering problems in the management and branch of the Muhammadiyah region in monitoring and evaluating its activities. The research method used is to use quantitative methods to obtain primary data to find out the user's desire for e-da'wah in Muhammadiyah citizens while the observation method and survey questionnaire are used to evaluate the acceptance of Muhammadiyah member users to the use of e-da'wah applications that have been made. This research aims to design a framework for the concept of web-based e-da'wah applications. As a result, the e-da'wah application model developed on a web-based basis has received responses from 57% of respondents who find it easy to understand the studies presented in this e-da'wah media.